Language ambiguity in high school science terminology - Poupová, Jana (Scientia in educatione, 2024)
The article deals with language ambiguity that appears in high school science terminology. Ambiguous terminology (homonyms and polysemic terms) creates difficulties in interdisciplinary communication, at school it can be a source of students’ misconceptions. The article presents a list of one-word ambiguous terms as they are presented in selected high school textbooks (biology, chemistry and physics). The list is (due to strictly defined criteria) not very long, nonetheless, it demonstrates the diversity of ambiguous terms, both in terms of their origin and the topic concerned (cross-discipline and intra-discipline ambiguity). Although many of these terms are marginal for high school students and their confusion is unlikely, the list gives evidence of multivalent ubiquity in scientific terminology. The article therefore offers recommendations on how the teacher should approach ambiguous terminology.